Analisis Pengendalian Waktu dan Biaya pada Proyek Pembangunan Gedung Medik RSU Assakinah Medika Menggunakan Earned Value Analysis - Wijaya, Eric Nora Setya; Triana, Masca Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Earned Value (EV) is a control method to measure the performance of a project from a time aspect in a sustainable manner and make cost estimates required until the project is completed and the project completion time. This method is one of the appropriate methods to be used in analyzing the Assakinah Medika Hospital Medical Building Construction project where the realization of the progress of the ongoing work on the project does not meet the plan, which only reaches 33.077% where the progress of the ongoing work should have reached 41.795% so that the project experiences a deviation of -8.718%.